Comparación de diferentes métodos de ajuste de la bicicleta en ciclistas entrenados: influencia de factores biomecánicos y energéticos - Ferrer Roca, B. (2015)
The performance in road cycling depends on several factors such as physiology (VO2Max, intensity, pedalling efficiency, fatigue, age, gender), environment (air-wind, atmospheric pressure, temperature, relative humidity, and the slope of the terrain) psychology, (self-talk, focus and teleoanticipation), training (strength, endurance, altitude training, heat acclimation, technique and tapering), nutrition (competitive nutritional strategy) and biomechanics (resistive forces, propulsive forces, pedalling kinematics and bicycle set-up). Although, the actual influence of some of these factors is still unknown, some studies have demonstrated the influence of proper bicycle configuration on aerodynamic drag, muscular coordinative pattern, pedal forces profile and, consequently, on energy expenditure. Saddle height and crank length are key factors in the lower limb kinetic change thus can contribute significantly on pedalling efficiency. There is some controversy in the specific cycling literature concerning theoptimal method to adjust saddle height. Anthropometric references (e.g. 106-109% of the inseam length) laid down on 70`s or 80`s (when toe-clip were mainly used) are still used today. The static goniometric method (cyclists should achieve a knee angle of 25-35º with the pedal located at the bottom dead centre) has been recommended in order to improve the anthropometric one. Furthermore, it has become increasingly frequent in recent years to use the dynamic goniometric method (2d analysis during pedalling), thanks to the introduction of new technologies. In this method, cyclists should achieve a knee flexion angle of 30-40º during pedalling) with the aim of optimizing muscle length and the lever arm, which vary with saddle height changes. In high-level cycling, small details can determine the final result. Moreover, at that level, the bicycle set-up is difficult to handle because the narrow range for possible modifications. To date, some studies have demonstrated the effect of wide changes in bicycle configuration on pedalling efficiency. However, the influence of small changes in factors such as saddle height or crank length remains unclear. The present Thesis would try to explain these issues by the following aims, addressed in four chapters: 1.- Verify if the anthropometric method (adjusting saddle height from 106% to 109% of the inseam length) ensure an optimal knee angle while pedalling (dynamic method), 2- Compare the static and dynamic goniometric methods in order to adjust the saddle height and analyse if the differences between methods are dependent of the relative saddle height, 3- evaluate the acute effects of small changes in saddle height on gross efficiency and lower-limb kinematics in well-trained cyclists, 4-analyse the acute effects of small changes in crank length on the energy cost of cycling and pedalling technique (kinetic and kinematic profiles) during submaximal pedalling Twenty three high-level male cyclists of the same team participated in the first study. Results support the view that adjusting saddle height from 106% to 109% of the inseam length (anthropometric method) does not ensure an optimal knee flexion angle (30-40º) while pedalling, because these references could be valid only to toe-clip pedals instead of clipless pedals. In fact, more than the half of the cyclists (56.5%) worked out with excessive knee flexion. Furthermore, a novel algorithm was proposed (SH = 22.1 + (0.896 · E) - (0.15 · KA)) that relates the inseam length (E) and the recommended knee angle while pedalling (KA) to set an optimal saddle height (SH) using the clip-less pedals. Thirteen well-trained cyclists participated in the second study. Static goniometric method (knee flexion angle of 25-35º) underestimated knee flexion (9-12º), hip flexion (4-7º) and plantar-flexion of the ankle (7-13º) compared with the dynamic method. In addition, the differences between both methods are dependent on the relative saddle height, mainly on knee and ankle joints. These findings suggest that using the static goniometric method could lead to misinterpretati on of the muscle length of the main muscles involved during cycling. Therefore, dynamic method is recommended instead of the static one, in order to ensure an optimal range of motion of the lower limb during pedalling. Furthermore, two-dimensional video analysis should be considered a useful tool to determine the kinematics of the cyclists, because it has a high correspondence with the three-dimensional analysis in the sagittal plane, is easy to use, and free software is available. Fourteen well-trained cyclists participated in the third study of this Thesis. They performed a submaximal pedalling test (~70-75% of the VO2max) at constant cadence (90 rpm).consisted on three randomized sets of 6 min with the preferred saddle height, 2% higher and 2% lower. The results of this study add to a growing body of literature that shows that changes in saddle height have acute effects on gross efficiency and on lower limb kinematics during pedalling. Raising the saddle height increased hip and knee joints extension and ankle plantarflexion (¡«4, 7 y 8o, respectively) more than the decrease in hip and knee joints flexion and ankle dorsiflexion (¡«3, 4 y 4o, respectively). Consequently the range of movement also increased (¡«1, 3 y 4o, respectively). Furthermore, gross efficiency changed significantly when lowering the saddle 4% from the higher to the lower position. Therefore, kinematic changes justified only part of the changes in pedalling efficiency. Finally, twelve road cyclists participated in the fourth study. The cyclists performed three sets of three submaximal pedalling repetitions (150, 200 and 250 W) at a constant cadence (~90 rpm) in order to analyse the effect of randomized changes in preferred crank length (¡À 5 mm) on physiological (energy cost of pedalling) and biomechanical variables (kinematic and kinetic profiles). A longer crank slightly increased both maximum torque during the downstroke (1.0-2.3 N¡¤m) and minimum torque during the upstroke, (1.0-2.2 N¡¤m) decreasing the positive impulse proportion (0.9-1.9%). Moreover, the flexion and the range of motion of both hip and knee increased (1.8-3.4o), while the ankle joint was not affected. A longer crank did not produce significant changes in the energy cost of cycling. Therefore, kinematic and kinetic changes due to a longer crank were not significant enough to alter the pedalling efficiency. The results of the present Thesis allow to draw the following conclusions: 1-static methods could be used as a first adjustment of saddle height, taking into account the new equation or the corrections proposed. The dynamic method should be introduced after the static evaluation to ensure a proper range of motion of the lower limb; 2- small changes in saddle height and in crank length produce significant changes on pedalling biomechanics that probably explain part of the metabolic changes. Likewise, pedalling efficiency is less sensitive to changes made.